Triboelectric nanogenerator to harness energy from low-frequency and low-amplitude vibrating sources (2025)
Dielectric Elastomer Generator (DEG) stands out as a promising electromechanical device to harness energy from non-conventional sources owing to its ability to convert mechanical energy into electrical power. DEG with no rotating part demonstrates a high performance-to-weight ratio with ease in fabrication and compactness that sets it apart from traditional energy harvesting techniques. Triboelectric nanogenerators (TENGs) belong to a self-powered class of DEG that capitalizes on low-frequency and amplitude mechanical sources. Existing models for predicting the performance of TENGs often assume parameters such as frequency, amplitude, and relative permittivity are constant. However, these parameters can vary depending on the specific application. In this study, a modified model is proposed to comprehensively investigate the performance of TENG in real-world conditions considering fluctuations in frequency, amplitude, and varying relative permittivity of elastomer layers. Results indicate that at a higher frequency of 55 Hz, there is a significant increase in output voltage, attributed to the higher energy release rate due to increased velocity. The study also emphasizes the role of the relative permittivity of TENG layers, revealing that elastomer layers with higher dielectric constants generate more voltage and power (151%) compared to those with lower values, particularly at a separation distance of 0.1mm. The findings of this study exhibit notable concurrence with previously reported values and offer a valuable framework for researchers seeking to tailor energy generators for enhanced performance and precision for harnessing energy from low-frequency and low-amplitude sources.